EDPRA: A screening instrument for assessing early pragmatic development - Botana Lois, Iria; Peralbo , Manuel (Revista de Investigación en Logopedia, 2023)
Pragmatics is one of the main indicators of impairments in communicative and social development in early childhood. The aim of the present study is to present a direct screening and performance test for the assessment of pragmatic development in children aged 6 to 48 months. Based on the approach of Dewart and Summers (1995), a pragmatic development screening scale was developed for the age ranges 6-12, 13-24, 25-36 and 37-48 months. Although it can be applied in its entirety throughout these stages, its clinical purpose is to check whether the development observed in the child corresponds to that expected in the normotypical population of his or her age. The scale contains items differentiated by age range in order to identify the dominant functions in each of them. Its psychometric properties were obtained from a total sample of 298 early childhood education participants of both sexes. Exploratory Factor Analysis identified the latent structure of the test, which can be described on the basis of the three axes proposed by Dewart and Summers, although with a different configuration of items. It has also been possible to confirm its adequate reliability and validity at all ages, and it has been possible to verify empirically how the weight of each factor varies in each age range.